Faktor-Faktor Yang Mempengaruhi Profitabilitas Bank Syariah Di Indonesia : Model Regresi Linear - Salsabila Firdaus; Dita Khoirunjannah; Nanda Mariyatul Qibtiyah (Cashless : Journal of Sharia Finance and Banking, 2025)
Operational risk is closely related to various issues arising from process weaknesses. This risk significantly impacts both the financial and non-financial aspects of Islamic banking profitability. This study employs a quantitative approach with multiple regression analysis to explore the effects of Capital Adequacy Ratio (CAR), Third-Party Funds (DPK), and Financing to Deposit Ratio (FDR) on Return on Assets (ROA) in Indonesian Islamic banks. The analysis reveals that CAR has a positive and significant impact on ROA, with a beta coefficient of 1.130 and a significance value of 0.007. Conversely, DPK and FDR exhibit no significant effects on ROA. These findings highlight the critical role of capital management in supporting the profitability of Islamic banks.